"Integrated reporting is like God: no one has met Him, but everybody talks about Him": The power of myths in the adoption of management innovations. Issue 5 (13th June 2018) - Gibassier, Delphine; Rodrigue, Michelle; Arjaliès, Diane-Laure
Abstract : Purpose: The purpose of this paper is to analyze the process through which an International Integrated Reporting Council (IIRC) pilot company adopted "integrated reporting" (IR), a management innovation that merges financial and non-financial reporting. Design/methodology/approach: A seven-year longitudinal ethnographic study based on semi-structured interviews, observations, and documentary evidence is used to analyze this multinational company's IR adoption process from its decision to become an IIRC pilot organization to the publication of its first integrated report. Findings: Findings demonstrate that the company envisioned IR as a "rational myth" (Hatchuel, 1998; Hatchuel and Weil, 1992). This conceptualization acted as a springboard for IR adoption, with the mythical dimension residing in the promise that IR had the potential to portray global performance in light of the company's own foundational myth. The company challenged the vision of IR suggested by the IIRC to stay true to its conceptualization of IR and eventually chose to implement its own version of an integrated report. Originality/value: The study enriches previous research on IR and management innovations by showing how important it is for organizations to acknowledge the mythical dimension of the management innovations they pursue to support their adoption processes. These findings, suggest that myths can play a productive role in transforming business (reporting) practices. Some transition conditions that make this transformation possible are identified and the implications of these results for the future of IR, sustainability, and accounting more broadly are discussed.